A Cidade (pós)moderna e suas tramas espaciais, temporais e afetivas nas narrativas literárias de Daniel Galera e Daniel Pellizzari - Linhares Neto, Guilherme (2009)
This dissertation aims to analyze the literary works of Daniel Galera and Daniel Pellizzari detecting influences of the urban space in their narratives from several perspectives: references to the architecture and social urban sphere; experience of the passages of time; pluralities of existences and perceptions thet subdue the inhabitants of the city. I also focus on understanding the space, stormy and affectionate woofs connected to the new millenniun’s urbanity that literature is able to reveal through its auto-referencial language. Galera and Pellizzari began to publish their books in the 2000’s – historical state of affairs in which the contemporany cities bring in a complementary and interactive way telecommunication networks and physical infrastructure – and initially were known through texts conveyed in the Internet. Besides the analysis of the narratives, another relevant issue of this paper is a historical trajectory on the constitution of the modernity and postmodernity in the city, and how technology permeates the daily life.